Sestrin2 Regulates Osteoclastogenesis via the p62-TRAF6 Interaction - Oh, Sue Young; Kang, Namju; Kang, Jung Yun; Kim, Ki Woo; Choi, Jong-Hoon; Yang, Yu-Mi; Shin, Dong Min (Frontiers in Cell and Developmental Biology, 2021)
The receptor activator of nuclear factor-kappa B ligand (RANKL) mediates osteoclast differentiation and functions by inducing Ca2+ oscillations, activating mitogen-activated protein kinases (MAPKs), and activating nuclear factor of activated T-cells type c1 (NFATc1) via the RANK and tumor necrosis factor receptor–associated factor 6 (TRAF6) interaction. Reactive oxygen species (ROS) also plays an important role during osteoclastogenesis and Sestrin2, an antioxidant, maintains cellular homeostasis upon stress injury via regulation of ROS, autophagy, and inflammation. However, the role of Sestrin2 in osteoclastogenesis remains unknown. In this study, we investigated the role of Sestrin2 in the RANKL-RANK-TRAF6 signaling pathway during osteoclast differentiation. Deletion of Sestrin2 (Sesn2) increased bone mass and reduced the number of multinucleated osteoclasts on bone surfaces. RANKL-induced osteoclast differentiation and function decreased in Sesn2 knock-out (KO) bone marrow-derived monocytes/macrophages (BMMs) due to inhibition of NFATc1 expression, but osteoblastogenesis was not affected. mRNA expression of RANKL-induced specific osteoclastogenic genes and MAPK protein expression were lower in Sesn2 KO BMMs than wild-type (WT) BMMs after RANKL treatment. However, the Sesn2 deletion did not affect ROS generation or intracellular Ca2+ oscillations during osteoclastogenesis. In contrast, the interaction between TRAF6 and p62 was reduced during osteoclasts differentiation in Sesn2 KO BMMs. The reduction in the TRAF6/p62 interaction and TRAP activity in osteoclastogenesis in Sesn2 KO BMMs was recovered to the WT level upon expression of Flag-Sesn2 in Sesn2 KO BMMs. These results suggest that Sestrin2 has a novel role in bone homeostasis and osteoclasts differentiation through regulation of NFATc1 and the TRAF6/p62 interaction.